Assessing the distributional impact of technical change in livestock and grains production in developing countries - Cranfield, J.A.L.; Hertel, Thomas W.; Preckel, P.V.; Reimer, J.J.; Ehui, Simeon K. (International Livestock Research Institute, 2002)
This paper outlines a general framework for analysing the distributional impact of commodity and factor price changes on the welfare of disaggregate households. The impact may be decomposed into an average effect and the departures from that average. The latter departures may be attributed to interactions between the commodity price changes and differences in consumption shares, on the one hand, and interactions between factor price changes and differences in factor earnings shares, on the other hand. Differences in consumption shares across households are estimated at the quintile level, using the International Comparisons Project (ICP) database in conjunction with the Deninger Squire database on income distribution. Estimated differences in factor income shares are obtained by combining information on total factor earnings, with observations on income by quintile, and initial estimates of the factor earnings pattern by quintile. Regional price impacts of technological change are estimated using the Global Trade Analysis Project (GTAP) model of global trade. We find that, in the case of Korea, Sri Lanka and Zambia, technological change in grains benefits the poorest house- holds relatively more than a comparable improvement in livestock productivity. The opposite is true in Thailand. With the exception of the Zambia livestock sector, technical progress in either livestock or grains benefits poorer households relatively more than their wealthier counterparts. While this stems primarily from their larger food consumption share, improvements in unskilled wages also play a role.